The Effect of Project Based Learning Model Assisted by Electronic Student Worksheet on Global Warming Material to Improve Creative Thinking Skills of Class X Students at SMA Negeri 2 Medan - Waruwu, Lilis Suryani; Motlan, Motlan (Universitas Negeri Padang, 2025)
The aim of this study was to determine whether there is an effect of using Project Based Learning model assisted by Electronic Student Worksheet (E-Worksheet) on students’ creative thinking skills in the global warning topic at Grade X of SMA Negeri 2 Medan. This research used a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 68 students of Grade X Phase E in the even semester at SMA Negeri 2 Medan, with 34 students in the experimental class and 34 students in the control class. Data collection was conducted using a creative thinking skills test based on four indicators: fluency, flexibility, originality, and elaboration. Data analysis included normality test, homogeneity test, and hypothesis testing. A one-tailed t-test on the post-test results showed that the t-count value of 3.761 exceeded the t-table value of 1.998, indicating a statistically significant difference between the experimental class was 82.79, higher than the control class average of 74.41. These results demonstrate that the implementation of the PjBL model assistes by E-Wroksheet significantly improves students’ creative thinking skills in learning global warming material compared to conventional learning methods.